Biochemistry of human tear film: A review. (July 2022) - Masoudi, Simin
Abstract: The precorneal tear film is a complex mixture of proteins, lipids, metabolites, and electrolytes with different structures and functionalities. Sustainable production of each tear component is vital to the health of the ocular surface. Abnormalities in the tear film components may reflect alterations in the health of the ocular surface or the presence of systemic disease. Despite all the research performed over the recent two decades, our knowledge of the tear film molecular profile in healthy individuals is scant and incomplete. The reported studies have mostly investigated small sample size populations in incomparably varying age groups and ethnic backgrounds. The methods used for detection and measurement of various tear compounds have been widely disparate making the comparison of results difficult. All these in addition to certain environmental factors are known to influence the resultant data. Therefore, studying normal human tear profile would require involvement of a wide range of sample population, factoring in age, race, gender, geographical and environmental parameters. Establishing a normal human tear profile may open the path to fast and simple diagnosis of disease, which in turn may lead to improved prognosis of treatments via early detection of disease. Highlights: The precorneal tear film is a complex mixture of proteins, lipids, metabolites, and electrolytes. The tear compounds have a range of different structures and functionalities. Sustainable production of each tear component is vital to the health of the ocular surface. Change in the tear biochemistry reflects alterations in the health of the eye or systemic disease. More research are required to establishing a normal human tear profile.